2005
DOI: 10.7249/mg304
|View full text |Cite
|
Sign up to set email alerts
|

The UN's Role in Nation-Building: From the Congo to Iraq

Abstract: The RAND Corporation is a nonprofit research organization providing objective analysis and effective solutions that address the challenges facing the public and private sectors around the world. RAND's publications do not necessarily reflect the opinions of its research clients and sponsors. R ® is a registered trademark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 3 publications
0
38
0
3
Order By: Relevance
“…The UN administration found that only about 70 Timorese citizens who still lived in the country had graduated from law school, while none of them had been practising law under the Indonesian control of the country. 40 Other sources confirm that the number of indigenous lawyers remaining after the referendum on independence was fewer than 10. 41 A similar situation has occurred in Kosovo, where the collapse of the law enforcement and the judicial system was pretty clear since the very beginning of the UN mission.…”
Section: Collapse Of the Previous Justice Systemmentioning
confidence: 93%
“…The UN administration found that only about 70 Timorese citizens who still lived in the country had graduated from law school, while none of them had been practising law under the Indonesian control of the country. 40 Other sources confirm that the number of indigenous lawyers remaining after the referendum on independence was fewer than 10. 41 A similar situation has occurred in Kosovo, where the collapse of the law enforcement and the judicial system was pretty clear since the very beginning of the UN mission.…”
Section: Collapse Of the Previous Justice Systemmentioning
confidence: 93%
“…Post-conflict statebuilding often refers specifically to efforts by external actors or donors to build or rebuild failed, weak or conflict-affected states (Brinkerhoff, 2007;Cox, 2001;Dobbins et al, 2001;Hartzel et al, 2003;Knoll, 2006;Milikin & Krause, 2002;Steffeck, 2003;Stewart, 2008). It can also encompass Fukuyama's (2004) more general notion of the formation of new governmental structures and the strengthening of existing institutions (see also Chandler, 2006;Englebert & Tull, 2008).…”
Section: Institutional Legitimacy In the Post-conflict Statementioning
confidence: 99%
“…9 This neoliberal state building model has been adopted after several military interventions since the end of the Second World War and its advocates argue that it is a rapid remedy for poverty, tyranny, and human rights violations. 10 As several scholars have pointed out, this model has mostly been deployed when a foreign power wants to minimise their post-conflict commitment by super-imposing their own preferred model of governance through the use of armed forces in the aftermath of a crisis. 11 This has led to a great deal of criticism of neo-liberal state building, including that it has not only proven to be ineffective, but that in some cases it can also exacerbate conflict by entrenching social, ethnic, political and ideological divides.…”
Section: Neo-liberal State Buildingmentioning
confidence: 99%